Comparative evaluation of morphological and chemical characteristics of bone after performing osteotomy with a piezoelectric device, hard tissue laser, and low-speed handpiece - Krishnaswamy, Vignesh; Dorairaj, Jayachandran; Gunasekaran, Srilekha; Ganesh, Sayee; Kesavan, Priya; Ramalingam, Kurinchichelvan (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Osteotomy procedures play a crucial role in achieving the desired osseous contour and elimination of the pocket. Traditional instruments such as chisels, files, and rotating burs have limitations including heat generation and tissue dam age. Novel instruments like piezoelectric and hard tissue lasers offer potential advantages in terms of precision and reduced tissue trauma. The aim of this study was to compare the chemical and morphological characteristics of bone surfaces after osteotomy procedures performed with three different instruments: piezoelectric, hard tissue laser, and low-speed handpiece. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Fifteen fresh cadaver bone specimens were randomly assigned to three groups: group A (piezoelectric), group B (hard tissue laser) and group C (low-speed handpiece). Osteotomy procedures were performed according to standard ized protocols. The specimens were determined under an energy-dispersive X-ray spectroscopy. Results. Analysis of morphological and chemical characteristics revealed significant differences in bone surface characteristics between groups. Groups A and B exhibited the smoothest surface with minimal tissue damage and microfractures. Group C showed the roughest surface with prominent microfractures and tissue damage. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Hard tissue laser and piezosurgery have shown better results due to greater precision as they preserved the bone mor phology, with less microfracture and chemical demineralization after osteotomy preparation compared with low-speed handpiece.